1995
DOI: 10.1073/pnas.92.21.9647
|View full text |Cite
|
Sign up to set email alerts
|

The VLA4/VCAM-1 adhesion pathway defines contrasting mechanisms of lodgement of transplanted murine hemopoietic progenitors between bone marrow and spleen.

Abstract: Selective lodgement or homing of transplanted hemopoietic stem cells in the recipient's bone marrow (BM) is a critical step in the establishment of long-term hemopoiesis after BM transplantation. However, despite its biologic and clinical significance, little is understood about the process of homing. In the present study, we have concentrated on the initial stages of homing and explored the functional role in vivo of some of the adhesion pathways previously found to mediate in vitro adhesion of hemopoietic ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
348
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(365 citation statements)
references
References 27 publications
15
348
2
Order By: Relevance
“…33,34 Indeed CD49d/VCAM-1 interactions have been shown to play an important role in the homing of progenitor cells back to the bone marrow. 35,36 It has previously been shown that CD49d expressed on neutrophils mediates interactions with VCAM-1 29 ; therefore, it is likely that neutrophil release is VCAM-1 dependent. However, there is also a precedent in the literature, in a model of chronic vasculitis, for CD49d/CD29-mediated neutrophil adhesion to be independent of VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 Indeed CD49d/VCAM-1 interactions have been shown to play an important role in the homing of progenitor cells back to the bone marrow. 35,36 It has previously been shown that CD49d expressed on neutrophils mediates interactions with VCAM-1 29 ; therefore, it is likely that neutrophil release is VCAM-1 dependent. However, there is also a precedent in the literature, in a model of chronic vasculitis, for CD49d/CD29-mediated neutrophil adhesion to be independent of VCAM-1.…”
Section: Discussionmentioning
confidence: 99%
“…Given the functional expression of b 1 integrins by mouse IEL, we sought to determine their importance in maintaining lymphocytes within the small intestinal epithelium. As b 1 deficiency is embryonically lethal and b 1 integrins are required for stem cell colonization of the BM [15][16][17], we utilized a model, recently described by Brakebusch et al [18], in which b 1 gene deletion is induced in lethally irradiated mice that have been reconstituted with BM derived from inducible b 1 -knockout mice [18]. Previous results have demonstrated that the number and phenotype of T cells in the spleen, lymph nodes, and peripheral blood of these mice is normal as is the homing and localization of b 1 -deficient T cells to the spleen, lymph nodes, and Peyer's patches [18].…”
Section: Mouse Small Intestinal Iel Express Functional B 1 Integrinsmentioning
confidence: 99%
“…Furthermore, in vivo experiments demonstrated that the pretreatment of animals with antia4 monoclonal antibodies (mAbs) inhibited engraftment of HSC during subsequent transplantation, and infusion of antia4 mAbs caused a robust mobilization of HSC into the peripheral blood (Papayannopoulou & Nakamoto, 1993;Papayannopoulou et al, 1995). More recent studies demonstrated that a chemokine, stromal cell-derived factor-1 [SDF-1, also termed CXCL12 according to a new classification system (Zlotnik & Yoshie, 2000)], plays a key role in the trafficking and homing of CD34 + cells to the marrow (Wright et al, 2002).…”
mentioning
confidence: 99%